Psychological peculiarities of anxiety and sanogenicity of the deprived person - Hoshovska, Daria; Hoshovskyi, Yaroslav (Psychological Prospects Journal, 2022)
Purpose. Determine the psychological features of anxiety and outline the necessity of sanogenity of a person who recognizes the negative and limiting impact of various types of deprivation. Methods. For the realization the purpose of the study we used the scientific and theoretical methods: analysis, synthesis, abstracting, generalization, that gave us the possibility to construct conceptual logical sequence between the key concepts and to state - the deprived person usually experiences various and multimodal anxiety, therefore thanks to acquisition of competences of sanogenic thinking it is capable to reach revitalizing effect and to establish more harmonious life. Results. Analysis of the scientific and psychological source base gave grounds to state that the variety of deprivation has a negative impact on the psychogenesis and sociogenesis of the person, in particular to increase their polymodal anxiety, which urgently requires the involvement of sanogenic revitalization approaches. Deprivation slows down and complicates personal development, causes an imbalance of affectivity, and negatively influences status-role identification. In the deprived person, the type of anxiety correlates with persistent (explicit or latent) feelings of guilt and stimulates hypertrophied introspection, self-injury, and so on. Staying in a state of deprivation only exacerbates personal anxiety, so there is an urgent need for sanogenic thinking, which involves activation of reflection as a mechanism for reducing the many discomforts and suffering from negative emotions and other psychosocial states. Conclusions. Deprived personality, experiencing feelings of neglect, abandonment and inferiority, is usually in a state of increased anxiety, which negatively affects their communication and life. Sanogenic thinking and reflection are an effective way out of the state of deprivation anxiety, which allows to achieve a favorable revitalizing effect.